Construindo pontes entre ciência e sociedade: divulgação científica sobre irradiação de alimentos - Denise S. Levy; Gian Maria Agostino Angelo Sordi; Anna Lucia Casanas Haasis Villavicencio (Brazilian Journal of Radiation Sciences, 2018)
Food irradiation is a safe and effective preservation technique to eliminate insects and parasites and reduce disease-causing microorganisms. The process helps to inhibit sprouting and delay ripening, prolonging the shelf-life of fresh fruits and vegetables. Nevertheless, among a great fraction of Brazilian population, there is still great misunderstanding about the peaceful applications of nuclear science. Most often the media and social networks tend to associate radiation to nuclear weapons and major accidents. Misinformation and common wrong beliefs confuse public’s perceptions: consumers seem to misunderstand the difference between irradiated food and radioactive food and the general public has major concerns about the negative health effects and environmental contamination. This paper presents some considerations about consumers´ perceptions of irradiated food, as well as the need of improving science communication. Society´s judgments and decision making are directly linked to perceived benefits and risks. The scientific community must build new bridges between nuclear science and the general public, offering a wider perspective on the benefits and risks resulting from ionizing radiation in everyday life.